Dependency of solid particle erosion behaviour of plasma sprayed NiTi coating on primary gas flow rate - B. Swain; S. Mantry; S.S. Mohapatra; P. Mallick; A. Behera (Applied Surface Science Advances)
Solid particle erosion is a major concern for the current generation aerospace industries. To reduce the effect of solid particle erosion on the aerospace engine parts, an NiTi coating has been developed by atmospheric plasma spray technology in the current investigation. Furthermore, the dependency of the solid particle erosion property on the primary gas flow rate of plasma spray coating has also been investigated. For this purpose, plasma spray coatings of NiTi alloy have been developed at different primary gas flow rates and various physical and mechanical properties have been evaluated. A correlation between the physical and mechanical properties of the coating with the solid particle erosion wear has been performed. Various phases have been obtained from the X-ray diffraction analysis such as NiTi-B2, Ni, Ti, Ni3Ti, Ti2Ni, NiO, TiO and Ni4Ti3, which also have been confirmed by energy dispersive spectroscopy method. From the microstructural investigation, various surface and interface defects such as unmelted particle formation, pores, microcracks, splat delamination etc. have been observed at the coatings developed at low primary gas flow rate and homogeneous splats have been observed from the coatings developed at higher primary gas flow rate. The coating developed at 40 lpm primary gas flow rate revealed the optimum properties like adhesion strength, microhardness, porosity, surface roughness etc. Erosion rate of the plasma sprayed NiTi coatings has been affected significantly by the coating's physical and mechanical properties. It has been revealed from the current investigation that the coating obtained from 40 lpm primary gas flow rate has less erosion rate as compared to others. Various erosion mechanisms such as groove formation, scratches, cutting, plastic deformation etc. has been observed from the microstructural analysis of the eroded samples at 45˚ impingement angle and splat fragmentation, splat delamination form the 90˚ impingement angle.